Laboratory Study on Vallejo and Scovazzo’s Methods in Estimating the Rheology Parameters of Bentonite and Kaolinite Muds - Budijanto Widjaja; Ignatius Tommy Pratama; Ian Hartono; Boby Limowa (Civil Engineering Dimension, 2024)
The mud undrained shear strength and viscosity are the essential parameters in understanding the behavior of mudflow. One of the laboratory test methods to estimate the undrained shear strength and viscosity is Vallejo and Scovazzo’s cylinder strength meter test (CSMT) and flume channel test, respectively. This paper compares the undrained shear strength of kaolin and bentonite muds obtained from the CMST to those obtained using the fall cone and mini vane shear tests and also studies the scale effects in the flume channel test in measuring the mud viscosity at a 20o to 40o slope angles and at various liquidity indexes. The results exhibit that CMST could estimate the undrained strength of mud as low as 0.45 kN/m2 with a liquidity index of up to 5.93. Then, the reduction of the size of the flume channel by half resulted in a mud viscosity of about 2.3 times higher.